The conundrum of causality and the criminal law (sexual offences and related matters) Amendment Act 32 of 2007 : a critical analysis - Carstens, Pieter Albert, 1960- (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2013.